2016
DOI: 10.1007/s00423-016-1459-3
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal stump closure using polymeric clips reduces intra-abdominal abscesses

Abstract: Closure of the appendiceal stump using the non-absorbable hem-o-lok ligation system did result in a reduced rate of intra-abdominal surgical abscesses as compared to the application of endoloops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
5
17
0
Order By: Relevance
“…Of those, 1082 records were excluded after screening for inappropriate article type; only randomized control trials and review articles were included, and those reporting key outcomes; 675 full text articles were then assessed for eligibility and 598 were excluded due to data being either inadequate for data interpretation, relating to interval appendectomy or duplication of studies. 77 were found to meet the inclusion criteria, and 45 of these were included for analysis after applying the MINORS score cut off . The modified PRISMA flowchart for identification and inclusion of relevant papers is included as Appendix S1.…”
Section: Resultsmentioning
confidence: 99%
“…Of those, 1082 records were excluded after screening for inappropriate article type; only randomized control trials and review articles were included, and those reporting key outcomes; 675 full text articles were then assessed for eligibility and 598 were excluded due to data being either inadequate for data interpretation, relating to interval appendectomy or duplication of studies. 77 were found to meet the inclusion criteria, and 45 of these were included for analysis after applying the MINORS score cut off . The modified PRISMA flowchart for identification and inclusion of relevant papers is included as Appendix S1.…”
Section: Resultsmentioning
confidence: 99%
“…The etiology of this complication remains unclear. On the one hand, some authors speculate that the occurrence of postoperative IAA might be influenced by several factors, such as advanced appendicular disease, appendicular perforation, the type of technique used for the removal of the appendix and the lack of an adequate perioperative antibiotics' regimen [4]. On the other hand, there are suggestions that a large-volume intraoperative peritoneal lavage might increase the rate of postappendectomy IAA [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted in order to evaluate the efficiency of polymer clips in minimally invasive surgery. Some studies have shown that it is possible to apply a double HOL to secure the base of the appendix during a laparoscopic appendectomy (5)(6)(7)(8), and many others have compared its effectiveness with LL and/or a stapler device in adults (9,10).…”
Section: Discussionmentioning
confidence: 99%